2009
DOI: 10.1002/ar.20821
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Associated mCherry Fluorescent Reporter Line for Studying Vascular Remodeling and Cardiac Function During Murine Embryonic Development

Abstract: The development of the cardiovascular system is a highly dynamic process dependent on multiple signaling pathways regulating proliferation, differentiation, migration, cell-cell and cell-matrix interactions. To characterize cell and tissue dynamics during the formation of the cardiovascular system in mice, we generated a novel transgenic mouse line, Tg(Flk1::myr-mCherry), in which endothelial cell membranes are brightly labeled with mCherry, a red fluorescent protein. Tg(Flk1::myr-mCherry) mice are viable, fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 19 publications
0
59
0
Order By: Relevance
“…Flk1-myr::mCherry Poché et al, 2009) and Flk1-H2B::eYFP (Fraser et al, 2005;Larina et al, 2009) (Huang et al, 2003;Lucitti et al, 2007). Embryos were genotyped using the following primers (5Ј-3Ј): mutant band, Mlc2a-mut-F (ACAGGGAATCACACCACCAT) and Mlc2a-mut-R (CGAACC -TGGTCGAAATCAG); wild-type band, Mlc2a-wt-F (GGCACGAT-CACTCAGTCAGA) and Mlc2a-wt-R (ATCCCTGTTCTGGTCAATGC).…”
Section: Mouse Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flk1-myr::mCherry Poché et al, 2009) and Flk1-H2B::eYFP (Fraser et al, 2005;Larina et al, 2009) (Huang et al, 2003;Lucitti et al, 2007). Embryos were genotyped using the following primers (5Ј-3Ј): mutant band, Mlc2a-mut-F (ACAGGGAATCACACCACCAT) and Mlc2a-mut-R (CGAACC -TGGTCGAAATCAG); wild-type band, Mlc2a-wt-F (GGCACGAT-CACTCAGTCAGA) and Mlc2a-wt-R (ATCCCTGTTCTGGTCAATGC).…”
Section: Mouse Linesmentioning
confidence: 99%
“…We used transgenic mice that fluorescently label the EC membranes (Flk1-myr::mCherry) and nuclei (Flk1-H2B::eYFP) and that label primitive blood cells (ε-Globin-GFP) (Dyer et al, 2001;Fraser et al, 2005;Larina et al, 2009;Poché et al, 2009). Using time-lapse imaging of dynamic events, as well as the analysis of cell death and proliferation in fixed embryos, we have found that vessel diameter increases do not result from changes in EC proliferation or survival.…”
Section: Introductionmentioning
confidence: 99%
“…To test the new hollow agarose cylinders in the light-sheet microscope, we imaged Flk1-myr::mCherry; Flk1-H2B::eYFP double-transgenic embryos (Fraser et al, 2005;Larina et al, 2009;Poché et al, 2009), in which endothelial cell (EC) membranes and nuclei were labeled with mCherry and yellow fluorescent protein (YFP), respectively, similar to our previous studies (Udan et al, 2013). For embryos between E8.5 and E9.5, we used agarose cylinders with a 4.7 mm outer diameter and a 2.5 mm inner diameter (see Materials and Methods).…”
Section: Light-sheet Imaging Of E85 Post-implantation Mouse Embryosmentioning
confidence: 99%
“…This enhancer was successfully used to drive mCherry expression in endothelial cells by other researchers [11,14]. However, deletion of this enhancer has no significant effect upon Flk1 expression in mesodermal progenitors at 7.5 dpc or in endothelial cells at 8.5 dpc [3].…”
Section: Introductionmentioning
confidence: 99%